2018
DOI: 10.1016/j.cjtee.2018.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Early and mid-term results of transarticular external fixation in the treatment of supination-external rotation type IV equivalent ankle fractures

Abstract: PurposeTo investigate the early and mid-term results of open reduction and internal fixation (ORIF) with transarticular external fixation (TEF) but no deltoid ligament repair (DLR) in the treatment of supination-external rotation type IV equivalent (SER IV E) ankle fractures (AO/OTA classification 44-B 3.1) and provide evidence for clinical practice.MethodsThis study cohort consisted of 22 patients with SER IV E ankle fractures that underwent ORIF with TEF but no DLR between December 2011 and December 2014. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Despite the difference in hospitalisation duration between HVCs and LVCs, the mean LOS ranks at the lower end of the described LOS in the literature [23,[27][28][29][30][31]. Regarding the differences in the LOS, a multicenter analysis from the Netherlands demonstrated longer hospitalisation at HVCs for fractures of the lower extremities.…”
Section: Discussionmentioning
confidence: 92%
“…Despite the difference in hospitalisation duration between HVCs and LVCs, the mean LOS ranks at the lower end of the described LOS in the literature [23,[27][28][29][30][31]. Regarding the differences in the LOS, a multicenter analysis from the Netherlands demonstrated longer hospitalisation at HVCs for fractures of the lower extremities.…”
Section: Discussionmentioning
confidence: 92%
“…As mentioned before, our previous study had shown that ORIF with TEF could achieve satisfactory outcomes in treating SER IV ankle fractures [15]. The present study retrospectively analyzed the results of 43 patients with SER IV ankle fractures who received ORIF with TEF (group 1) or ORIF with DLR (group 2).…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies had shown that transarticular external fixators might raplace the plaster casts well by offering the opportunity for self-healing of deltoid ligament and allowing early weight bearing [12–14]. Our previous study had also shown that open reduction and internal fixation (ORIF) with transarticular external fixation (TEF) but no DLR could achieve satisfactory outcomes in treating SER IV ankle fractures [15].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies had shown that transarticular external fixators might raplace the plaster casts well by offering the opportunity for self-healing of deltoid ligament and allowing early weight bearing [12][13][14]. Our previous study had also shown that open reduction and internal fixation (ORIF) with transarticular external fixation (TEF) but no DLR could achieve satisfactory outcomes in treating SER IV ankle fractures [15].…”
Section: Introductionmentioning
confidence: 97%